Cover Image, Volume 39, Issue 1. Issue 1 (7th December 2017) - Marsh, Ashley P. L.; Edwards, Timothy J.; Galea, Charles; Cooper, Helen M.; Engle, Elizabeth C.; Jamuar, Saumya S.; Méneret, Aurélie; Moutard, Marie‐Laure; Nava, Caroline; Rastetter, Agnès; Robinson, Gail; Rouleau, Guy; et al.
Abstract : On the cover : This cover image, by Ashley P. L. Marsh et al., is based on the Mutation Update DCC mutation update: Congenital mirror movements, isolated agenesis of the corpus callosum, and developmental split brain syndrome, Pages 23–39. DOI:10.1002/humu.23361 .